2016 Neonatal Nurse Practitioner Workforce Survey: Report of Findings. (October 2017) - Staebler, Suzanne; Bissinger, Robin
Abstract : The National Association of Neonatal Nurse Practitioners (NANNP) conducted its second workforce survey of certified neonatal nurse practitioners in the fall of 2016. National Association of Neonatal Nurse Practitioners partnered with the National Certification Corporation and the American Association of Nurse Practitioners to conduct this electronic survey, containing 69 questions and focusing on practice sites and total compensation packages (including benefits) and workforce deficits. Findings indicate a rising neonatal nurse practitioners (NNPs) position vacancy rate across the country. Regional salary data indicated that the southeast had lower compensation rates for NNPs, with regions 4 and 11 (South) having the lowest rates. A promising trend indicated that new graduate NNPs with a doctorate are earning more. The study findings indicate that tailoring benefit packages to the age and years of experience for the individual NNP may aid in recruiting and retaining NNPs in practice. For experienced NNPs, altered shift lengths (shorter), higher employer matching rates in retirement plans, and less employee cost sharing for health insurance benefits are more appealing strategies. It is critical for NNPs to continually evaluate the profession's workforce data. There are more than 205, 000 nurse practitioners practicing in the United States, with neonatal NPs making up approximately 3% of the larger whole. Increased participation in future surveys will assist in creating sustainable solutions to the workforce crisis facing the profession.